Development of Multiple Intelligence Based Interactive Ebook to Improve Critical Thinking Ability and Cognitive Learning Outcomes on an Excretory System - Septiana, Renny; Yulianti, Evy; Nurcahyo, Heru (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to produce a feasible interactive ebook based on multiple intelligence for 11th-grade students of Senior high school, determine the effectiveness of an interactive ebook based on multiple intelligence on excretion system to improve the critical thinking ability of 11th-grade students of Senior High School, determine the effectiveness of interactive ebook based multiple intelligence on excretion system to improve cognitive learning outcomes of 11th-grade students of Senior High School. The multiple intelligence-based interactive ebooks are designed by Flip PDF Corporate application with html5 output converted to the android application by web2apk. The method used for this development was research and development (R&D) with the 4D (Define, Design, Develop and Disseminate) research model. The sampling method for the study was conducted random sampling. Method using one experiment class and one control class. This research in SMA Negeri 1 Ngemplak. Data Collection Techniques were using interviews, visionary, pre-test, and post-test. Ebook validation was carried out by material and media validators. The data analysis technique used a quasi-experimental non-equivalent control group design with the multivariate test by IBM SPSS 24. The ebook has validation and got 92,6% from the biology teacher, that is mean the ebook is valid and possible to use in biology learning. The Effect size shows 0.290 for critical thinking and 0.159 for cognitive learning outcomes, which means ebook has a high effect on both abilities